AGROWISATA PERTANIAN DI KECAMATAN KERTAK HANYAR KALIMANTAN SELATAN - Ihsanul Hakim; Naimatul Aufa (ULM Press, 2021)
Agriculture is an important sector for the State of Indonesia which is an agricultural country and most of its population works in this sector. However, the rapid development of industry and technology has made the agricultural sector less attractive to the public. Banjar Regency, South Kalimantan, which is the main food supplier district in South Kalimantan, has also experienced this, agricultural land has begun to decrease due to changing functions, the number of workers in the agricultural sector has decreased every year and the profession of farmers is less attractive to the young generation. Agro-tourism design in Kertak Hanyar District aims to increase the interest of the younger generation in the agricultural sector by combining agricultural activities with tourism activities located in agricultural areas. By using the concept of recreational and educational architecture which aims to provide a better psychological experience when visiting agricultural land.